2003
DOI: 10.1093/jxb/erg247
|View full text |Cite
|
Sign up to set email alerts
|

Cold-specific and light-stimulated expression of a wheat (Triticum aestivum L.) Cor gene Wcor15 encoding a chloroplast-targeted protein

Abstract: Wcor15, a member of the wheat cold-responsive (Cor) gene family, has been isolated and characterized. The deduced polypeptide WCOR15 (MW=14.7 kDa) showed high homology to the previously identified wheat and barley COR proteins. Southern blot analysis using diploid, tetraploid and hexaploid wheat and diploid Aegilops species showed that the wheat and related wild genomes possessed multiple copies of Wcor15 homologues. Five copies were assigned to the homologous group 2 chromosomes by nulli-tetrasomic analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 43 publications
4
69
2
Order By: Relevance
“…It has been reported that the constitutive overexpression of COR15 enhances the frost tolerance of the chloroplast and reduces the damage to photosystems in non-acclimating plants (Artus et al 1996) and it is known that COR15a is transported into the chloroplast and accumulates in the stromal compartment (Shimamura et al 2006) where it acts in a dehydrin-like manner. Sun et al (2009) thought that Mo maintained the activity of the photosynthetic system through the regulation of the redox state in wheat chloroplasts (Takumi et al 2003). Sun et al (2006) and Yu et al (2006) also found that low-temperature stress and deficiency of Mo decreased the rate of net photosynthesis (Pn), and the application of Mo enhanced frost tolerance as well as photosynthesis through the regulation of ABA-independent COR gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the constitutive overexpression of COR15 enhances the frost tolerance of the chloroplast and reduces the damage to photosystems in non-acclimating plants (Artus et al 1996) and it is known that COR15a is transported into the chloroplast and accumulates in the stromal compartment (Shimamura et al 2006) where it acts in a dehydrin-like manner. Sun et al (2009) thought that Mo maintained the activity of the photosynthetic system through the regulation of the redox state in wheat chloroplasts (Takumi et al 2003). Sun et al (2006) and Yu et al (2006) also found that low-temperature stress and deficiency of Mo decreased the rate of net photosynthesis (Pn), and the application of Mo enhanced frost tolerance as well as photosynthesis through the regulation of ABA-independent COR gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR-amplified fragment was digested with HindIII and XbaI and replaced by the CaMV35S promoter of pBI121 (Clontech) to produce Wdhn13::GUS constructs. The Wcor15::GUS construct containing 1.7-kb 5' upstream region was after Takumi et al (2003). The Wcbf2 cDNA sequence was amplified with the following primer set in addition to the XbaI or SacI linker; 5'-CCCTCTAGATTGACGCTGCA-ACTGATGGA-3' and 5'-CCCGAGCTCCGGATTATTAGT-TCCAAAGC-3'.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of the other wheat Cor/Lea genes including Wcor14 , Wcs19 , Wlt10 and Wcs120 is also ABA-independent (Houde et al, 1992;Tsvetanov et al, 2000;Ohno et al, 2001;NDong et al, 2002). The conserved CRT/DRE-like sequence motifs were found in the promoter regions of the Wcor15 and Wcs120 genes, and their promoter sequences were proven to be LT-inducible in both monocotyledonous and dicotyledonous transgenic plants Takumi et al, 2003). These results strongly suggest that the functional Cor/Lea gene system involving the CBF/DREB1 trans -acting factors and the CRT/DRE cis element is conserved in wheat.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The products of these genes are localized in the chloroplasts (Chauvin et al 1993). Although their functions are still unclear, Takumi et al (2003) proposed that these proteins maintain the activity of the photosynthetic apparatus under cold conditions. The expression of these genes is strongly influenced by the light conditions or the presence of electrontransport inhibitors, suggesting that their expression is regulated by the photosystem II reduction/oxidation (redox) state (Dal Bosco et al 2003, NDong et al 2001.…”
Section: Introductionmentioning
confidence: 99%